Outcomes of external DCR with primary silicone stent intubation in cases of chronic dacryocystitis - Sunil G Biradar; Mariam Mercy Varghese (Wolters Kluwer Medknow Publications, 2020)
Background: Since the introduction of external dacryocystorhinostomy (DCR) as one among the treatment modalities for chronic dacryocystitis, various treatment modifications have been developed with the goal of attaining the best possible post-surgical outcomes. The use of silicone tube intubation is one of them. But it's an effect on patency of the lacrimal system during external DCR in cases of primary nasolacrimal duct obstruction (NLDO), canalicular obstruction or in revision surgeries is still controversial. Objective: To evaluate the outcomes of external dacryocystorhinostomy (DCR) with primary silicone stent intubation in patients with a history of chronic dacryocystitis. Methods: A prospective cross-sectional study involving data of 18 patients with chronic dacryocystitis who underwent external DCR with primary silicone stent intubation from May 2018 to May 2019. Postoperative follow-ups were at 1 week,1,3 and 6 months. The stents were removed at 3 months. Subjective and objective assessments on each visit were done by asking for symptoms of epiphora, checking for sac regurgitation and patency by syringing. Results: Complications like a recurrence of epiphora, infection, loss or extrusion of stents etc. were not reported. Three patients experienced mild discomfort post-intubation with no watering and the sac was patent on syringing. Two patients had minimal watering but the sac was patent on the syringing indicating absence of blockage of the nasolacrimal duct. Conclusion: External DCR with primary silicone stent intubation is a successful procedure for the treatment and prognosis of chronic dacryocystitis. Overall the surgical outcomes were successful.